Facile fabrication of low-content surface-assembled MXene in silicone rubber foam materials with lightweight, wide-temperature mechanical flexibility, improved flame resistance and exceptional smoke suppression - Chen, Hai-Yang; Li, Yang; Wang, Peng-Huan; Qu, Zhang-Hao; Qin, Yu-Qing; Yang, Ling; Li, Jia-Yun; Gong, Li-Xiu; Zhao, Li; Zhang, Guo-Dong; Gao, Jie-Feng; Tang, Long-Cheng (Composites. Part A, Applied science and manufacturing, 2024)
Silicone rubber foam (SiRF) is a promising porous material that is widely applied in various fields. However, its intrinsic flammability nature remains a significant challenge. One of the simplest and most economical solutions is to incorporate high content flame-retardant fillers. Unfortunately, such approach is limited by several drawbacks, including poor filler dispersion, difficulty in processing and negative effect on mechanical flexibility. Herein, we report a green and facile strategy for surface-assembling ultralow content of MXene sheets bonded onto the pore surface of SiRF via the effective foaming reaction process. The as-prepared MSiRF-0.2 composite at 0.2 wt% MXene exhibited lightweight characteristic, wide-temperature mechanical flexibility, UL94-V0 grade, limited oxygen index of >27%, and exceptional smoke suppression (reduction by 88.24%). Furthermore, flame-retardant mechanism was discussed based on the char structure observation. This study provides a novel approach for fabricating mechanically flexible and flame-retardant SiRF via in-situ reactive assembly of low content MXene sheets.